2018
DOI: 10.1016/j.mad.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

HIV antiretroviral therapy drugs induce premature senescence and altered physiology in HUVECs

Abstract: Developments in medicine have led to a significant increase in the average human lifespan. This increase in aging is most readily apparent in the case of HIV where antiretroviral therapy has shifted infection from a terminal to a chronic but manageable disease. Despite this advance, patients suffer from co-morbidities best described as an accelerated aging phenotype. A potential contributor is cellular senescence, an aging-associated growth arrest, which has already been linked to other HIV co-morbidities such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The question remains as to whether the effect of TDF on neuronal mitochondrial function is direct or mediated through activation of microglia and astroglia. Previous studies suggest that TDF can affect neurons directly 16,72 . Our data clearly show that TDF has robust effects on glial activation both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The question remains as to whether the effect of TDF on neuronal mitochondrial function is direct or mediated through activation of microglia and astroglia. Previous studies suggest that TDF can affect neurons directly 16,72 . Our data clearly show that TDF has robust effects on glial activation both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 96%
“…These data are consistent with studies by Cohen et al . that showed ART can induce inflammatory gene expression and cellular senescence in astroglia and endothelial cells 72,73 . Therefore, we hypothesize that TDF affects neuronal mitochondrial function directly and also through activation of glia.…”
Section: Discussionmentioning
confidence: 99%
“…HIV patients on ART exhibit changes in endothelial functions, such as lower expression levels of von Willebrand Factor or protein S (Chwiki et al 2017 ). A combination of Tenofovir and Emtricitabine can act as cellular stressors, leading to endothelial cell senescence, as demonstrated by a reduction in proliferation, and an increase in inflammatory markers (Cohen et al 2018 ). This results in decreased BBB integrity and impaired endothelial cell functions.…”
Section: Art-induced Bbb Dysfunctionmentioning
confidence: 99%
“…Although implementation of ART has decreased the severity of HAND, it still remains prevalent, with over 50% of HIV-1-infected patients exhibiting mild symptoms of HAND (Chai et al, 2017). Because HAND remains prevalent even in the ART era, it has been suggested that viral replication is not a major factor involved in mediating cognitive decline (Zeitler et al, 2015;Berman et al, 2016;Dickens et al, 2017;Cohen et al, 2018). The viral protein HIV-1 Tat therefore, has been highlighted as a potential viral product that may contribute to the development of HAND (Chen et al, 1997;Eugenin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular Tat is biologically active and can cause induction of apoptosis, oxidative stress, and release of pro-inflammatory cytokines and neurotransmitters, all of which may contribute to the development of HAND (Table 1; Henderson et al, 2019;Ajasin and Eugenin, 2020). Additionally, the presence of Tat alone in the CNS of animal models is sufficient to replicate HAND pathologic and behavioral changes (Zeitler et al, 2015;Berman et al, 2016;Dickens et al, 2017;Cohen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%